Marjinalisasi Perempuan Pertama Melalui Lagu: Suatu Analisis Wacana Kritis Terhadap Lagu “Jadikan Aku Yang Kedua” - Endang Setiowati; Bhernadetta Pravita Wahyuningtyas (Humaniora, 2011)
During 2006 until 2007 there were plenty of songs that are lyrical about adultery or polygamy, in line also with the emergence of the phenomenon of polygamy and infidelity by some famous people ranging from businessmen, preachers, politicians, to academics. One of the most popular songs is a song titled “Jadikan Aku yang Kedua”. Surprisingly, although the title shows that this song legalized polygamy, the majority of listeners who request the song to be played in radio stations are women. The research reveals about the marginalization of women that is implicitly contained in a song lyrics. The research method used is critical discourse analysis with analytical techniques using the model of Norman Fairclough. This study uses substantive theoreticalframework such as hegemony, ideology, patriarchy, and feminism and the discourse analysis theory from Michael Foucault. The results showed that the Song is a discourse to marginalize women who occupy the first position, while for the second women or femme fatale, this song is empowering them. Song writer has the power to shape the ideology of consumer (listener) toward his patriarchal ideology. He wants to use his power to encourage the women to dare to become a femme fatale.